Molecular analysis of GJB2 (connexin 26) and GJB6 (connexin 30) gene mutations in non-syndromic hereditary deafness in South Africa - Whitehead, Caragh (Caragh Bryony) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.